An Act prescribing the rules and conduct to be observed with respect to Negroes and other Slaves of this territory, in A General Digest of the Acts of the Legislature of Louisiana, Passed from the Year 1804 to 1827, at 104 (1828) - (:unkn) unknown (My University, 1806)
20: Prohibited any person who keeps "slaves for the purpose of hunting" from delivering to any "slaves" any firearm for the purpose of hunting without permission.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES